If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6 = -5z + -6 Reorder the terms: -6 = -6 + -5z Add '6' to each side of the equation. -6 + 6 = -6 + 6 + -5z Combine like terms: -6 + 6 = 0 0 = -6 + 6 + -5z Combine like terms: -6 + 6 = 0 0 = 0 + -5z 0 = -5z Solving 0 = -5z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '5z' to each side of the equation. 0 + 5z = -5z + 5z Remove the zero: 5z = -5z + 5z Combine like terms: -5z + 5z = 0 5z = 0 Divide each side by '5'. z = 0 Simplifying z = 0
| -2+3=-5 | | 2x-9=24-21x | | z/6+3=z/5+2 | | .80(D-100)=D-50 | | m/4=m/12+8/3 | | 18x-25x=1/3 | | .80(D-100)=D-100 | | (9/16)/(7/10) | | 9/16/7/10 | | 2x^4-5x^3-x^2-5x-3=0 | | 56=7(24-x) | | y-6=-5x+50 | | 4(v+2)=6v+12 | | 2x-4=3(x+1) | | 8x^2-6x+10=0 | | (z/2)^2 | | -72=-6y | | 4t-5/-9=7 | | 3/7-k/3=8/21 | | -21+p=4 | | y/3=y/7+4 | | x+y=95 | | x/2-x=2 | | 7/12x=-4/36 | | -5/12y=-2/5 | | p/-4=-44 | | 7z=1/7 | | 4/2m-m=4+1/2m | | 3=-6*1+-3 | | -5(6x+4)=-200 | | 3x^8/x^4 | | 7/6y=42 |